Comparison of efficiency of 1% permethrin lotion vs. 0.5% ivermectin shampoo in the treatment of pediculosis capitis - Monisha, B. M.; Madhumitha, M.; Thilagavathi, S. (International Journal of Research in Dermatology, 2018)
Background: Pediculosis or head louse infestation is a common condition and an issue of concern in developing countries. Various treatment options are available for the management of this condition but still needs further research due to drug resistance. This study seeks to compare the efficacy of 1% permethrin lotion and 0.5% ivermectin shampoo in the management of pediculosis capitis. Methods: A prospective longitudinal study was conducted in a tertiary care hospital from September 2013 to June 2015. Patients presenting with pediculosis capitis infestation were divided into two groups of 50 each. They were treated with either topical 1% permethrin lotion or 0.5% ivermectin shampoo. Follow up was done once in 4 weeks on the extent of head lice infestation. Results: After being treated with either topical 1% permethrin or 0.5% ivermectin shampoo, the presence of nits decreased significantly in the ivermectin group. Number of patients either had no nits or less than 5 dead nits in the permethrin group than in the ivermectin group. Conclusions: It is concluded that both 1% permethrin and 0.5% ivermectin have comparable efficacies in managing pediculosis capitis infestation, but permethrin was found to be more effective in treatment. In addition, none of the participants in both the treatment groups experienced any side effects. This is one of the very few studies exploring the treatment efficacy of topical ivermectin and the potential scope for future studies on the treatment options for pediculosis capitis.